Transpancreatic Hepatomesenteric Trunk Complicating Pancreaticoduodenectomy - Rammohan, Ashwin; Sathyanesan, Jeswanth; Palaniappan, Ravichandran; Govindan, Manoharan (JOP. Journal of the Pancreas, 2013)
Context Standard celiac and hepatic arterial anatomy occur in approximately 60% of the patients; for the remaining, multiple variations have been described. A thorough knowledge of these anomalies is important in order to avoid unnecessary complications. In this report we describe one of the rarest arterial anomalies, a hepatomesenteric trunk supplying the liver. We attempt to elucidate its implications pertaining to the safe performance of a pancreaticoduodenectomy. Case report A 45-year-old male with a one-month duration painless progressive jaundice was evaluated and diagnosed as having a periampullary growth. Preoperative imaging did not suggest any arterial anomalies. Intraoperatively, the common hepatic artery was found to originate from the superior mesenteric artery. He underwent a pylorus preserving pancreaticoduodenectomy with a meticulous dissection and preservation of the aberrant hepatomesenteric trunk. His postoperative period was uneventful and is doing well on follow up. Conclusion Variations in hepatic and celiac arterial anatomy are common, and may not get picked up on preoperative imaging. A high index of suspicion in every patient along with a precise knowledge of the normal anatomy and awareness of the aberrant anatomy is a sine qua non to the performance of a safe pancreaticoduodenectomy. Image: Post pancreaticoduodenectomy-preserved hepatomesenteric trunk.